Applying nursing process: a case study of a pregnant patient of 31.6 weeks, premature rupture of membranes and twin pregnancy - Chura Muñuico, Ruth (2019)
Premature Rupture of Membranes (PROM) is a complication of pregnancy that causes 40% of pre-term birthsand carries 10% of neonatal mortality. This study aimed to implement the nursing process in the care of a 31.6week old pregnant woman, Premature Rupture of Membranes, Twin pregnancy, history of fertilization in vitrioand UTI treatment, in Obstetrics and Gynecology Service Room “B” National Teaching Hospital Child MotherSt. Bartholomew in the period November –December 2011. Data was obtained after the evaluation of MarjoryGordon´s functional patterns, later diagnosed by The NANDA Taxonomy II International 2012 – 2014, a modelfounded by Virginia Herdenson. The following nursing diagnoses for standardized care plan are as follows: Riskof impaired fetal maternal Dyad, Ineffective peripheral tissue perfusion, Risk of infection, Acute pain, Anxiety,Impaired physical mobility, sleep pattern disorder, Self-care deficit: bathing, toilet use, Risk for impaired skinintegrity, Risk for dysfunctional gastrointestinal motility and Willingness to better manage their own health.The process of nursing care is important because it has an impact on the profession, the patient and nurse;Professionally process defines the focus of nurses working in clinical practice, with a view to enhance the qualityof life of the patient through quality care and thus further strengthen the work of nursing.